If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = 2(2c + -5) * c Reorder the terms: 8 = 2(-5 + 2c) * c Reorder the terms for easier multiplication: 8 = 2c(-5 + 2c) 8 = (-5 * 2c + 2c * 2c) 8 = (-10c + 4c2) Solving 8 = -10c + 4c2 Solving for variable 'c'. Reorder the terms: 8 + 10c + -4c2 = -10c + 10c + 4c2 + -4c2 Combine like terms: -10c + 10c = 0 8 + 10c + -4c2 = 0 + 4c2 + -4c2 8 + 10c + -4c2 = 4c2 + -4c2 Combine like terms: 4c2 + -4c2 = 0 8 + 10c + -4c2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(4 + 5c + -2c2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(4 + 5c + -2c2)' equal to zero and attempt to solve: Simplifying 4 + 5c + -2c2 = 0 Solving 4 + 5c + -2c2 = 0 Begin completing the square. Divide all terms by -2 the coefficient of the squared term: Divide each side by '-2'. -2 + -2.5c + c2 = 0 Move the constant term to the right: Add '2' to each side of the equation. -2 + -2.5c + 2 + c2 = 0 + 2 Reorder the terms: -2 + 2 + -2.5c + c2 = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -2.5c + c2 = 0 + 2 -2.5c + c2 = 0 + 2 Combine like terms: 0 + 2 = 2 -2.5c + c2 = 2 The c term is -2.5c. Take half its coefficient (-1.25). Square it (1.5625) and add it to both sides. Add '1.5625' to each side of the equation. -2.5c + 1.5625 + c2 = 2 + 1.5625 Reorder the terms: 1.5625 + -2.5c + c2 = 2 + 1.5625 Combine like terms: 2 + 1.5625 = 3.5625 1.5625 + -2.5c + c2 = 3.5625 Factor a perfect square on the left side: (c + -1.25)(c + -1.25) = 3.5625 Calculate the square root of the right side: 1.887458609 Break this problem into two subproblems by setting (c + -1.25) equal to 1.887458609 and -1.887458609.Subproblem 1
c + -1.25 = 1.887458609 Simplifying c + -1.25 = 1.887458609 Reorder the terms: -1.25 + c = 1.887458609 Solving -1.25 + c = 1.887458609 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '1.25' to each side of the equation. -1.25 + 1.25 + c = 1.887458609 + 1.25 Combine like terms: -1.25 + 1.25 = 0.00 0.00 + c = 1.887458609 + 1.25 c = 1.887458609 + 1.25 Combine like terms: 1.887458609 + 1.25 = 3.137458609 c = 3.137458609 Simplifying c = 3.137458609Subproblem 2
c + -1.25 = -1.887458609 Simplifying c + -1.25 = -1.887458609 Reorder the terms: -1.25 + c = -1.887458609 Solving -1.25 + c = -1.887458609 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '1.25' to each side of the equation. -1.25 + 1.25 + c = -1.887458609 + 1.25 Combine like terms: -1.25 + 1.25 = 0.00 0.00 + c = -1.887458609 + 1.25 c = -1.887458609 + 1.25 Combine like terms: -1.887458609 + 1.25 = -0.637458609 c = -0.637458609 Simplifying c = -0.637458609Solution
The solution to the problem is based on the solutions from the subproblems. c = {3.137458609, -0.637458609}Solution
c = {3.137458609, -0.637458609}
| 13z+9=8-3z+2 | | 2x=(1/50) | | 12q=6 | | 6v^2-100=10v | | 3ln(2x+8)=14 | | 10p-7+2-1=3+5 | | 1/11 | | 2/7=x/100 | | 40x-9=71 | | 3t+10=4t+5 | | -7y+7-6=-14y+6-4 | | (-8.946)(14.08)= | | 5x+8=41 | | equals= | | X^3+7x^2=x^2+16x | | n=3/4 | | (X^3)+(3x^2)-8x=0 | | y=(3/5*-2)-2/3 | | y=3/5×-2-2/3 | | 9x-7=6-4+5 | | (-12/47)(-47/24)= | | (-12/47)(-47/12)k= | | (16x)^(1/2) | | 5x+(-5+9)=-3 | | 16x+8y=85 | | x^2y-x^2+16y=0 | | (16-2x)(12-2x)=96 | | h=-0.44t^2+2.2t+10 | | y=-.6*55+22 | | y=-0.6*45+22 | | g(x)=4x^3 | | y=-.06*35+22 |